Study of UHECR deflections in the presence of the galactic magnetic field JF2012 - Santos, Larissa Cristina; Cássia dos Anjos, Rita de (Cadernos de Astronomia, 2024)
The production and acceleration of high-energy cosmic rays (Ultra-high energy cosmic rays - UHECR) in the Universe remains one of the great mysteries of modern science. The mechanisms of acceleration of highly energetic particles in astrophysical sources are still unknown. The main objective of this study was to explore the distribution of UHECR emission and arrival originating from radio galaxies. The radio galaxies Centaurus A, Fornax A and M87 were used as possible sources due to their correlation with the direction of arrival of events measured at the Pierre Auger Observatory. The detection potential of these particles was explored considering the effect of the Jansson-Farrar 2012 (JF2012) Galactic magnetic field model. The study of the influence of the magnetic field helps to understand the generation and propagation of UHECR. For the study, the computational program Cosmic Ray Transport (CRT) was used. The program does not consider energy losses, but was used to quantify particle deviations based on the following parameters: energy rigidity, distance from the source to the Earth, direction of the source in the sky and charge/mass of the particle to be propagated. The results obtained quantify the effect of the Galactic magnetic field in the different directions of radio galaxies and indicate that the Galactic field must be considered from energies close to 16 EeV.